Selective hydrogenation catalyst as well as preparation method and application thereof
By regulating the oxygen-containing groups and supported active components on the surface of the support, a high-performance carbon four-selective hydrogenation catalyst was prepared, which solved the problems of uneven distribution of active metals of the existing catalyst and poor thickness controllability, and achieved the effect of high metal utilization and long life.
Patent Information
- Application Number
- CN202311198137.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-15
AI Technical Summary
The existing carbon four-selective hydrogenation catalyst has low distribution uniformity and poor thickness controllability, making it difficult to meet the requirements of high metal utilization, high performance and long life.
By controlling the types and amounts of oxygen-containing groups on the surface of the support, an alumina-containing support is prepared, and the main active components such as Pd and Ni and co-active components are supported on the surface to form a selective hydrogenation catalyst.
The dispersion of the catalyst and the uniform distribution of active components are improved, the performance of the catalyst is enhanced, and the higher butadiene selectivity and metal utilization are achieved.
Smart Images

Figure BDA0004453947360000101 
Figure BDA0004453947360000111 
Figure BDA0004453947360000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a selective hydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, with the increase and expansion of ethylene plants, ethylene production has increased year by year, and the amount of by-product C4 has also increased rapidly. At present, most of the by-product C4 of ethylene plants is mainly utilized through extraction to produce butadiene, etherification to produce MTBE and separation of 1-butene, 2-butene and other processes, but there is also a common situation that butadiene tail gas containing alkynes and some residual C4 are not fully utilized. Among them, the C4 alkyne tail gas with low utilization rate accounts for about 2wt% of the C4 production capacity, and often needs to be diluted and discharged to the flare, which has a large amount of greenhouse gas emissions, resource waste and safety problems. Through selective hydrogenation, the alkynes in the C4 alkyne tail gas can be hydrogenated to produce butadiene or butene for utilization. Therefore, the selective hydrogenation catalyst plays a key role in the full utilization of C4 resources.
[0003] Chinese patent CN111054388A discloses a C4 selective hydrogenation catalyst and its preparation method. The catalyst uses a mixture of magnesium aluminum spinel and pseudo-boehmite and then crushed powder as a carrier, Ni-Ag as an active component, and uses an impregnation method to load the active component. After loading, a pore-expanding agent and other molding aids are added to extrusion molding. The addition of magnesium aluminum spinel reduces the isomerization activity of 1-butene while ensuring the conversion rate of butadiene.
[0004] Chinese patent CN110813288A discloses a preparation method and application of a C4 alkyne selective hydrogenation catalyst. The patent uses a coprecipitation method to prepare a precursor, then adds a binder and a pore-forming agent to extrude and prepare a ZrO2 / CdO / Bi2O3 composite carrier, and uses an equal volume impregnation method to load the active component Re-Pd-La. The catalyst reduces olefin loss while improving butadiene selectivity, alkyne conversion rate and anti-poisoning performance.
[0005] Chinese patent CN114308059A discloses a C4 selective hydrogenation catalyst. The catalyst uses alumina with a bimodal pore distribution structure as a carrier, with a small pore size of 10-45nm and a large pore size of 80-500nm. Its main active component Pd is loaded by microemulsion and solution method, and the active component loaded by the microemulsion method is mainly distributed in the macropores. Long-term evaluation shows that the catalyst has excellent anti-coking ability.
[0006] In the existing technical solutions, the active metal distribution uniformity of C4 selective hydrogenation catalyst is low, the thickness controllability is poor, and it is difficult to achieve the requirements of high metal utilization, high performance and long life. By controlling the type and number of oxygen-containing groups on the surface of the carrier, the performance of the C4 selective hydrogenation catalyst prepared by using the carrier is improved accordingly. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention proposes a novel C4 fraction selective hydrogenation catalyst, which is used for the selective hydrogenation of C4 fractions to convert alkynes into butadiene.
[0008] One of the objects of the present invention is to provide a selective hydrogenation catalyst, comprising a carrier containing aluminum oxide, and a main active component supported on the carrier containing aluminum oxide, wherein the main active component is selected from at least one of the elements of Group VIII, and the surface oxygen-containing group density of the carrier containing aluminum oxide is 0.3 to 6 mmol / m 2 The alumina-containing carrier contains other inorganic compounds in addition to alumina.
[0009] According to the present invention, in the selective hydrogenation catalyst:
[0010] The main active component is selected from at least one of Pd and Ni;
[0011] Based on the weight of the alumina-containing carrier being 100%, the weight of the main active component is 0.1 to 25%, preferably 0.2 to 20%;
[0012] The catalyst optionally contains an auxiliary active component, which may be a metal auxiliary active component commonly used in the art. Preferably, the auxiliary active component is at least one of Au, Zn, Pb, Sn, Ag, Cu, alkali metals, and alkaline earth metals. In addition to the metal elements listed above, other commonly used active metal elements, such as rare earth elements, may also be used. The weight of the auxiliary active component is 0 to 10%, preferably 0.01 to 5%, based on the weight of the carrier as 100%.
[0013] The alumina-containing carrier can be used alone or optionally in combination with other inorganic compounds. For example, based on the weight of the alumina-containing carrier being 100%, the alumina-containing carrier also contains 0 to 30% of other inorganic compounds, and the other inorganic compounds are selected from at least one of titanium dioxide, silicon oxide, magnesium oxide, barium oxide, calcium oxide, and hydrotalcite.
[0014] According to the present invention, in the selective hydrogenation catalyst, the alumina-containing carrier contains abundant oxygen-containing groups. Preferably, the oxygen-containing group density on the surface of the alumina-containing carrier is 0.5 to 6 mmol / m 2; The surface oxygen-containing groups may be at least one of hydroxyl, carboxyl, and lactone groups, wherein the content of the hydroxyl group is 3 to 60 mmol / g, the content of the carboxyl group is 3 to 50 mmol / g, and the content of the lactone group is 3 to 40 mmol / g;
[0015] The specific surface area of the alumina-containing carrier is 20 to 250 m 2 / g, water absorption rate is 40-120%, carrier strength is 60-170N / particle, bulk density is 0.45-0.95g / ml, and pore volume is 0.40-1.6ml / g.
[0016] The second object of the present invention is to provide a method for preparing the above-mentioned selective hydrogenation catalyst, comprising: mixing a solution containing a metal compound of a main active component and a metal compound of an optional auxiliary active component with a carrier containing alumina, and drying and calcining to obtain the above-mentioned selective hydrogenation catalyst.
[0017] According to the present invention, in the method for preparing the selective hydrogenation catalyst:
[0018] The metal compound of the main active component is selected from at least one of chlorides, nitrates, acetates, sulfates, and metal organic compounds of Group VIII elements, preferably at least one of chlorides, nitrates, acetates, sulfates, and metal compounds of Pd and Ni;
[0019] The metal compound of the auxiliary active component is selected from at least one of Au, Zn, Pb, Sn, Ag, Cu, alkali metals, alkaline earth metal chlorides, nitrates, acetates, sulfates, and metal organic compounds;
[0020] The solvent in the solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid and alcohols.
[0021] According to the present invention, in the method for preparing the selective hydrogenation catalyst:
[0022] The metal compound solution can be loaded on the carrier by spraying and / or impregnation;
[0023] The drying conditions are: drying at 60-180°C for 6-15h, preferably, drying at 80-160°C for 8-12h;
[0024] The calcination conditions are: calcination at 250-650° C. for 4-12 h, preferably, calcination at 300-600° C. for 6-10 h.
[0025] According to the present invention, the alumina-containing carrier is obtained by the following preparation method: mixing components including an aluminum source, a forming agent, a pore expanding agent, functional carbon, and optionally other inorganic compounds, adding a binder to knead and shape, drying, roasting, and then surface treating to obtain the alumina-containing carrier.
[0026] According to the present invention, in the method for preparing the alumina-containing carrier:
[0027] The aluminum source is selected from at least one of boehmite, pseudo-boehmite, γ-alumina, α-alumina, θ-alumina, and aluminum hydroxide;
[0028] The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and starch;
[0029] The pore-enlarging agent is selected from at least one of sesbania powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide, and polypropylene glycol;
[0030] The functional carbon is selected from at least one of coke, activated carbon, carbon black, white carbon, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond;
[0031] The other inorganic compound is selected from at least one of titanium dioxide, silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite;
[0032] The binder is a solution containing at least one of nitric acid, sulfuric acid, hydrochloric acid, oxalic acid, acetic acid and ascorbic acid, and the solvent in the solution is selected from at least one of water, ethanol, ethylene glycol and ethylenediamine;
[0033] The amount of the functional carbon is 1 to 40 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the contained Al2O3;
[0034] The amount of the forming agent used is 1 to 15 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the Al2O3 contained;
[0035] The amount of the pore expanding agent is 1 to 15 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the Al2O3 contained;
[0036] In parts by mass, the amount of the other inorganic compound is 0 to 30 parts relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the contained Al2O3.
[0037] According to the present invention, in the method for preparing the alumina-containing carrier:
[0038] Before the surface treatment, the kneaded material is dried. The drying process can be carried out using the drying equipment and drying conditions commonly used in the prior art. For example, the drying process is carried out at 40 to 140° C. for 1 to 12 hours, preferably at 60 to 120° C. for 2 to 8 hours.
[0039] The surface treatment is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation, wherein:
[0040] The heat treatment conditions are as follows: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa;
[0041] The crystallization conditions are: temperature of 120-250°C, time of 4-18h, pressure of 0.2-15MPa, and the solvent used for crystallization is selected from at least one of water, ethanol, ethylene glycol, and ethylenediamine;
[0042] The oxidation conditions are: temperature of 30-80°C, time of 0.2-10h, the oxidant solution used for oxidation is selected from at least one of nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant solution is 0.1-10 mol / L;
[0043] The alkalization conditions are as follows: the temperature is 30-110° C., the time is 0.2-10 h, the alkaline solution used for alkalization is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline solution is 0.1-10 mol / L;
[0044] The irradiation conditions are as follows: the ray source is selected from gamma rays and / or microwaves, preferably, the gamma ray irradiation dose rate is 2-90 kGy / min, and the time is 0.2-24 h; the microwave power is 50-1000 W, and the time is 0.5-60 min.
[0045] In the present invention, the alumina and its preparation can refer to patent ZL202311028071.8, and the relevant contents disclosed in the aforementioned document are introduced into the present invention as a reference. In the preparation process of the alumina-containing carrier, heat treatment, crystallization, oxidation, irradiation treatment or introduction of carbon species are adopted to change its crystal structure, surface isoelectric point and local Al-O charge density to increase the types and quantity of oxygen-containing groups in the carrier.
[0046] The third object of the present invention is to provide an application of the above selective hydrogenation catalyst or the selective hydrogenation catalyst obtained by the above preparation method in the selective hydrogenation reaction of C4 fraction. The "C4 fraction selective hydrogenation" refers to the process of converting alkynes into butadiene by selective hydrogenation.
[0047] According to the present invention, the C4 fraction is a high-acetylene tail gas produced by a butadiene device, wherein the C4 fraction has a 1,3-butadiene content of 3 to 60 wt%, a vinyl acetylene content of 0.5 to 30 wt%, and an ethyl acetylene content of 0.1 to 10 wt%; in the selective hydrogenation reaction, the molar ratio of unsaturated hydrocarbons in the C4 fraction to H2 is 1:(0.5 to 1), preferably 1:(0.8 to 1), wherein the unsaturated hydrocarbons in the C4 fraction are calculated based on the total molar amount of unsaturated alkynes and dienes contained therein, and include 1,3-butadiene, vinyl acetylene, ethyl acetylene, etc.;
[0048] The conditions for the selective hydrogenation reaction include: the reactor inlet temperature is 35-45°C, the reactor pressure is 0.6-3MPa, the liquid feed space velocity based on the C4 fraction raw material is 30-50h -1 .
[0049] The present invention provides a C4 fraction selective hydrogenation catalyst, the catalyst comprising an alumina-containing carrier, a main active component, and an optional auxiliary active component. The alumina-containing carrier contains abundant oxygen-containing groups, and the oxygen-containing group density on the carrier surface is 0.3-6 mmol / m 2 , the alumina-containing carrier contains other inorganic compounds in addition to alumina. The present invention can produce anchor points by regulating the type and amount of oxygen-containing groups on the carrier, so that more active sites are exposed while reducing agglomeration during the calcination process, improving the dispersion of the catalyst, and making the active components more evenly distributed, thereby improving the performance of the catalyst. The catalyst provided by the present invention can selectively hydrogenate alkynes in the C4 fraction into butadiene, and by regulating the type, amount and density of oxygen-containing groups on the carrier, the distribution of metal active components is controlled, and the metal utilization rate is improved to obtain better butadiene selectivity. DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0051] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0052] Example 1
[0053] 1. Preparation of molding carrier
[0054] Weigh 100 g of pseudo-boehmite (specific surface area 246.3 m 2 / g, pore volume 0.89ml / g, bulk density 0.26g / ml), 25g α-Al2O3 powder, 5.4g hydroxypropyl methylcellulose, 6g starch, 12g coconut shell ash, put into a kneader and mix evenly. Weigh 1.0g concentrated nitric acid and 0.5g citric acid, add 100ml deionized water to prepare a mixed solution. Add the prepared solution into a kneader, knead and extrude into pellets to obtain cylindrical particles with a particle size of 2-4mm. Dry the particles at 80℃ for 8h, crystallize at 160℃ for 5h, soak them in 1.5mol / L potassium permanganate for 3h, and then dry them at 80℃ for 8h to obtain the alumina-containing carrier S1.
[0055] 2. Preparation of Selective Hydrogenation Catalyst
[0056] 0.09 g of zinc nitrate was weighed and added to 1.6 mL of palladium nitrate solution (Pd content was 25 mg / mL), diluted to 12.0 mL with deionized water, and sprayed onto 20 g of alumina-containing carrier S1. The sprayed sample was placed in an oven and dried at 120° C. for 10 h, and then calcined at 550° C. for 8 h to obtain catalyst C1, whose Pd loading was 0.2 wt % and Zn loading was 0.1 wt %.
[0057] Example 2
[0058] 1. Forming carrier preparation
[0059] Weigh 100g of pseudo-boehmite, 20g of γ-Al2O3, 6g of polyvinyl alcohol, and 10g of white carbon black in Example 1, put them into a kneader and mix them evenly. Weigh 2.2g of concentrated nitric acid and 8g of carboxymethyl cellulose and add them to 130g of deionized water, mix them evenly to prepare a mixed solution. Add the prepared solution into a kneader, knead it, extrude it into pellets, and obtain cylindrical particles with a particle size of 2-4mm. Dry the particles at 120℃ for 8h, heat treat them at 400℃, 0.6MPa of acetylene and nitrogen (volume ratio 0.06:1) for 5h, and finally irradiate them with 60w microwave for 10min to obtain the alumina-containing carrier S2.
[0060] 2. Preparation of Selective Hydrogenation Catalyst
[0061] 12 g of nickel nitrate and 0.32 g of silver nitrate were weighed, diluted to 13.2 mL with deionized water, and sprayed onto 20 g of alumina-containing carrier S2. The sprayed sample was placed in an oven and dried at 120° C. for 10 h, and then calcined at 550° C. for 8 h to obtain catalyst C2, whose Ni loading was 12 wt % and Ag loading was 1 wt %.
[0062] Example 3
[0063] 1. Preparation of molding carrier
[0064] Weigh 100g of pseudo-boehmite in Example 1, 15g of alumina trihydrate, 4g of sesbania powder, 6g of polyethylene glycol cellulose, and 5g of charcoal, put them into a kneader and mix them evenly. Then weigh 1g of concentrated sulfuric acid and 0.5g of ascorbic acid and add them to 115g of deionized water to prepare a mixed solution. Add the prepared solution into a kneader, knead and extrude it into pellets to obtain cylindrical particles with a particle size of 2-4mm. After drying the particles at 100°C for 6h, soak them in 1mol / L potassium hydroxide solution for 2h, dry them according to the above conditions and soak them in 2mol / L hydrogen peroxide for 2h, and dry them at 80°C for 8h to obtain the alumina-containing carrier S3.
[0065] 2. Preparation of Selective Hydrogenation Catalyst
[0066] 0.05 g of lead nitrate was weighed and added to 1.6 mL of palladium nitrate solution (Pd content was 25 mg / mL), diluted to 14.5 mL with deionized water, and sprayed onto 20 g of alumina-containing carrier S3. The sprayed sample was placed in an oven and dried at 120° C. for 8 h, and then calcined at 550° C. for 8 h to obtain catalyst C3, whose Pd loading was 0.20 wt % and Pb loading was 0.15 wt %.
[0067] Example 4
[0068] Weigh 100g of pseudo-boehmite, 6g of starch, 4g of sesbania powder, 4g of polyvinyl alcohol, and 7g of graphyne in Example 1 and put them into a kneader and mix them evenly. Then weigh 1g of acetic acid and 1g of concentrated nitric acid and add them to 105g of deionized water to prepare a mixed solution. Add the prepared solution into a kneader, knead, extrude and granulate to obtain cylindrical particles with a particle size of 2-4mm. Dry the particles at 80°C for 6h, crystallize at 200°C and 3Mpa for 15h, and then irradiate them with γ-rays at 3kGy / min for 10h to obtain a carrier S4 containing aluminum oxide.
[0069] 2. Preparation of Selective Hydrogenation Catalyst
[0070] 0.19 g of copper nitrate was weighed and added to 1.6 mL of palladium nitrate solution (Pd content was 25 mg / mL), diluted to 13.7 mL with deionized water, and sprayed onto 20 g of alumina-containing carrier S4. The sprayed sample was placed in an oven and dried at 120° C. for 9 h, and then calcined at 550° C. for 8 h to obtain catalyst C4, whose Pd loading was 0.20 wt % and Cu loading was 0.25 wt %.
[0071] Example 5
[0072] Weigh 100g of pseudo-boehmite in Example 1, 20g of TiO2, 3g of ethyl cellulose, 5g of starch, 6g of polypropylene glycol, and 9g of activated carbon into a kneader and mix well. Weigh 3g of citric acid and add it to 130g of deionized water to prepare a mixed solution. Add the prepared solution into the kneader, knead and extrude it into pellets to obtain cylindrical particles with a particle size of 2-4mm. Dry at 100℃ for 5h, heat treat at 300℃, 3MPa of carbon dioxide and nitrogen (volume ratio 0.3:1) for 2h, immerse in 1.5mol / L ammonium persulfate solution for 3h, and then dry at 80℃ for 8h to obtain the alumina-containing carrier S5.
[0073] 2. Preparation of Selective Hydrogenation Catalyst
[0074] 3 ml of aqua regia solution (Au content of 10 mg / ml) and 1.6 ml of palladium nitrate solution (Pd content of 25 mg / ml) containing gold were weighed, diluted to 12.6 ml with deionized water, and sprayed onto 20 g of alumina-containing carrier S5. The sprayed sample was placed in an oven and dried at 120°C for 12 hours and then calcined at 550°C for 8 hours to obtain catalyst C5, whose Pd loading was 0.20 wt% and Au loading was 0.15 wt%.
[0075] Comparative Example 1
[0076] The carrier was prepared according to the method of Example 1, except that coconut shell ash was not added during the molding process, to obtain carrier S6. The catalyst was prepared according to the method of Example 1, to obtain catalyst D1.
[0077] Comparative Example 2
[0078] The carrier was prepared according to the method of Example 1, except that the carrier was not subjected to crystallization and oxidation after drying. The dried carrier was placed in a muffle furnace and calcined at 1200° C. for 5 h to obtain carrier S7. The catalyst was prepared according to the method of Example 1 to obtain catalyst D2.
[0079] Comparative Example 3
[0080] Take the commercially available specific surface area of 90.5m 2The finished alumina with a bulk density of 0.61 g / ml, a strength of 52.4 N / particle and a water absorption rate of 69.8% was used as carrier S8. A catalyst was prepared according to the method of Example 1 to obtain catalyst D3.
[0081] Comparative Example 4
[0082] The commercially available carrier S8 was immersed in 3.0 mol / L potassium permanganate for 4 h, dried at 120° C. for 8 h, and then treated with a 300 W microwave for 40 min to obtain the carrier S9. The catalyst was prepared according to the method of Example 1 to obtain the catalyst D4.
[0083] Test Example 1 Carrier Characterization
[0084] The specific surface area was measured by nitrogen physical adsorption BET method;
[0085] The bulk density was calculated by measuring the mass of 100 mL of the carrier containing alumina, and the average value was taken after measuring each sample three times;
[0086] The strength was measured using a universal particle strength measuring instrument, and the average value of the measurement results of 20 carrier particles was taken;
[0087] The water absorption rate is obtained by taking 20 g of a carrier containing aluminum oxide, immersing it in water for 10 minutes, taking it out and draining the surface water, and measuring the weight increase.
[0088] The nature and quantity of oxygen-containing groups in the carrier were determined by Boehm chemistry.
[0089] Table 1. Physical property measurement results of alumina-containing carriers in Examples and Comparative Examples
[0090]
[0091] The oxygen-containing groups of the carriers of the embodiments and comparative examples were analyzed and determined. Three portions of 0.6 g of the carrier were weighed and soaked in 40 ml of 0.05 mol / L NaHCO3, Na2CO3 and NaOH solutions for 24 h, respectively. 10 ml of the soaked solution was titrated with 0.05 mol / L hydrochloric acid. Each sample was titrated three times, and the arithmetic mean was taken. The number of various oxygen-containing groups of the carrier was calculated based on the consumption of alkali, and the oxygen-containing group density was obtained in combination with the carrier specific surface data. The results are listed in Table 2.
[0092] Table 2. Measurement results of oxygen-containing groups on alumina-containing carriers in Examples and Comparative Examples
[0093]
[0094] It can be seen from Table 2 that the content and density of oxygen-containing groups on the surface of the support containing aluminum oxide prepared by the method of the present invention are significantly higher. At the same time, by adjusting the raw material ratio, preparation process parameters and conditions, the method of the present invention can achieve the regulation of the number and distribution of oxygen-containing groups on the surface of the support containing aluminum oxide.
[0095] Test Example 2 Catalytic Performance Evaluation of Catalyst
[0096] 20 ml of the catalysts in the above Examples 1 to 5 and Comparative Examples 1 to 4 were respectively added into an adiabatic fixed bed reactor and evaluated under the following conditions. The evaluation results are shown in Table 3.
[0097] Among them, gas chromatography is used to detect the component contents of the C4 fraction raw material and the material after selective hydrogenation using various catalysts, and the butadiene selectivity is calculated according to the following formula.
[0098] Butadiene selectivity = (butadiene out -Butadiene in ) / (vinyl acetylene in -Vinyl acetylene out )*100%
[0099] The evaluation conditions are as follows: the C4 fraction feedstock is fed into the selective hydrogenation reactor from top to bottom, the reactor inlet temperature is 40°C, the pressure is 2.0 MPa, the molar ratio of hydrogen to acetylene in the mixed flow at the inlet is 0.87:1, the vinyl acetylene content at the reactor inlet is 2.71 wt%, and the liquid space velocity (LHSV) calculated based on the feed amount of the C4 fraction feedstock is 40 h -1 .
[0100] Table 3 Composition of C4 fraction
[0101]
[0102] Table 4 Catalyst evaluation results
[0103]
[0104] The contents of alkynes and olefins in the hydrogenated products in Table 4 are the weight percentages calculated after deducting the hydrogen content. The results of using the above catalyst for selective hydrogenation of C4 fractions show that the catalyst of the present invention has better selectivity and higher catalytic utilization of metal atoms.
Claims
1. A selective hydrogenation catalyst comprising an alumina-containing carrier and a main active component supported on the alumina-containing carrier, wherein the main active component is selected from at least one of the elements of Group VIII, and the surface oxygen-containing group density of the alumina-containing carrier is 0.3 to 6 mmol / m 2 The alumina-containing carrier contains other inorganic compounds in addition to alumina.
2. The selective hydrogenation catalyst according to claim 1, characterized in that The main active component is selected from at least one of Pd and Ni; and / or, Based on 100% weight of the alumina-containing carrier, the weight of the main active component is 0.1 to 25%, preferably 0.2 to 20%; and / or, The catalyst optionally contains an auxiliary active component, preferably, the auxiliary active component is at least one of Au, Zn, Pb, Sn, Ag, Cu, alkali metals, and alkaline earth metals; and / or, based on the weight of the carrier as 100%, the weight of the auxiliary active component is 0 to 10%, preferably 0.01 to 5%; and / or, Taking the weight of the alumina-containing carrier as 100%, the alumina-containing carrier contains 0 to 30% of other inorganic compounds in addition to alumina, and the other inorganic compounds are selected from at least one of titanium dioxide, silicon oxide, magnesium oxide, barium oxide, calcium oxide, and hydrotalcite.
3. The selective hydrogenation catalyst according to claim 1, characterized in that The oxygen-containing group density on the surface of the alumina-containing carrier is 0.5 to 6 mmol / m 2 and / or, The specific surface area of the alumina-containing carrier is 20 to 250 m 2 / g, water absorption rate is 40-120%, carrier strength is 60-170N / particle, bulk density is 0.45-0.95g / ml, and pore volume is 0.40-1.6ml / g.
4. A method for preparing the selective hydrogenation catalyst according to any one of claims 1 to 3, comprising: The selective hydrogenation catalyst is obtained by mixing a solution containing a metal compound of a main active component and a metal compound of an optional auxiliary active component with a carrier containing aluminum oxide, drying and calcining.
5. The preparation method according to claim 4, characterized in that: The metal compound of the main active component is selected from at least one of chlorides, nitrates, acetates, sulfates and metal organic compounds of Group VIII elements, preferably at least one of chlorides, nitrates, acetates, sulfates and metal organic compounds of Pd and Ni; and / or, The metal compound of the co-active component is selected from at least one of Au, Zn, Pb, Sn, Ag, Cu, alkali metals, alkaline earth metal chlorides, nitrates, acetates, sulfates, and metal organic compounds; and / or, The solvent in the solution is selected from at least one of water, hydrochloric acid, nitric acid, acetic acid and alcohols; and / or, The drying conditions are: drying at 60-180°C for 6-15h, preferably, drying at 80-160°C for 8-12h; and / or, The calcination conditions are: calcination at 250-650° C. for 4-12 h, preferably, calcination at 300-600° C. for 6-10 h.
6. The preparation method according to claim 4, characterized in that: The alumina-containing carrier is obtained by the following preparation method: mixing components including an aluminum source, a molding agent, a pore-enlarging agent, functional carbon, and other inorganic compounds that are optionally added, adding a binder and kneading them into a shape, and then performing surface treatment to obtain the alumina-containing carrier.
7. The preparation method according to claim 6, characterized in that: In the method for preparing the alumina-containing carrier: The aluminum source is selected from at least one of boehmite, pseudo-boehmite, γ-alumina, α-alumina, θ-alumina, and aluminum hydroxide; and / or, The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and starch; and / or, The pore-enlarging agent is selected from at least one of sesbania powder, polyvinyl alcohol, polyethylene glycol, polyacrylamide and polypropylene glycol; and / or, The functional carbon is selected from at least one of coke, activated carbon, carbon black, white carbon, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; and / or, The other inorganic compound is selected from at least one of titanium dioxide, silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite; and / or, The binder is a solution containing at least one of nitric acid, sulfuric acid, hydrochloric acid, oxalic acid, acetic acid and ascorbic acid, and the solvent in the solution is selected from at least one of water, ethanol, ethylene glycol and ethylenediamine; and / or, The amount of the functional carbon is 1 to 40 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the Al2O3 contained; and / or, The amount of the forming agent used is 1 to 15 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the Al2O3 contained; and / or, The amount of the pore expanding agent is 1 to 15 parts by mass relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the Al2O3 contained; and / or, In parts by mass, the amount of the other inorganic compound is 0 to 30 parts relative to 100 parts of the aluminum source, wherein the aluminum source is calculated based on the contained Al2O3.
8. The preparation method according to claim 6, characterized in that: In the method for preparing the alumina-containing carrier, the surface treatment is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation.
9. The preparation method according to claim 8, characterized in that: The heat treatment conditions are as follows: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa; and / or, The crystallization conditions are: temperature of 120-250° C., time of 4-18 hours, pressure of 0.2-15 MPa, and the solvent used for crystallization is at least one selected from water, ethanol, ethylene glycol, and ethylenediamine; and / or, The oxidation conditions are: temperature of 30-80° C., time of 0.2-10 h, the oxidant solution used for oxidation is selected from at least one of nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant solution is 0.1-10 mol / L; and / or, The alkalization conditions are: temperature of 30-110° C., time of 0.2-10 h, the alkaline solution used for alkalization is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the solution concentration is 0.1-10 mol / L; and / or, The irradiation conditions are: the ray source is selected from gamma rays and / or microwaves, preferably, the gamma ray irradiation dose rate is 2-90 kGy / min, the time is 0.2-24 h; and / or the microwave power is 50-1000 W, the time is 0.5-60 min.
10. Use of the selective hydrogenation catalyst according to any one of claims 1 to 3 or the selective hydrogenation catalyst obtained by the preparation method according to any one of claims 4 to 9 in the selective hydrogenation reaction of a C4 fraction.
11. The use according to claim 10, characterized in that: In the C4 fraction, the content of 1,3-butadiene is 3-60wt%, the content of vinyl acetylene is 0.5-30wt%, and the content of ethyl acetylene is 0.1-10wt%; and / or, In the selective hydrogenation reaction, the molar ratio of unsaturated hydrocarbons in the C4 fraction to H2 is 1:(0.5-1), preferably 1:(0.8-1), wherein the unsaturated hydrocarbons in the C4 fraction are calculated based on the total molar amount of unsaturated alkynes and dienes contained therein; and / or, The conditions of the selective hydrogenation reaction include: the reactor inlet temperature is 35-45°C, the reactor pressure is 0.6-3MPa, the liquid feed space velocity based on the C4 fraction raw material is 30-50h -1 .
Citation Information
Patent Citations
Catalyst for preparing butadiene through selective hydrogenation of C4 alkyne, preparation method and applications thereof
CN110813288A
Nickel-based C4 fraction selective hydrogenation catalyst and preparation method thereof
CN111054388A
Alkyne-rich C4 fraction selective hydrogenation catalyst
CN114308059A
Alumina carrier as well as preparation method and application thereof
CN119500087A
Catalyst for C4 fraction selective hydrogenation and removal of alkyne, and preparation method thereof
CN102240548A